PENGARUH KOMPENSASI DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA KARYAWAN PT KHARISMA BERKAH NUSANTARA BEKASI JAWA BARAT - Zulfia, Rayhan Atalla; Tumanggor, Rahmayanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to find out whether there is a positive and significant influence between Compensation and Extrinsic Motivation either partially or simultaneously on employee performance at PT Kharisma Berkah Nusantara Bekasi, West Java. This study uses a quantitative research method where the data obtained is in the form of a questionnaire processed using the SPSS 2.2 application. The results There is an effect of Compensation on employee performance at PT Kharisma Berkah Nusantara Bekasi West Java It is shown by the regression equation Y = 51.911 + 0.252 X1, below the value of the correlation coefficient (R) of 0.309 which means that the coefficient between variables X1 to Y is low, The calculated value of the Compensation variable is 0.066 smaller than the ttable value of 2.002 with a level of 0.0 smaller than 0.05, then it can be interpreted that Ha is accepted and H0 is rejected, so that it can be partially concluded that compensation has a positive and significant effect on employee performance, There is an effect of extrinsic motivation on employee performance at PT Kharisma Berkah Nusantara Bekasi West Java as shown by the regression equation Y = 34,028 + 0.250 X2, the value of the correlation coefficient (R) is 0.560 which means the coefficient between variables X2 to Y is moderate. The tcal value of the Extrinsic Motivation variable is 4.408 greater than the ttable of 2.002 with a significant level of 0 less than 0.05, then it can be interpreted that Ha is accepted and H0 is rejected. So that it can be partially concluded that Extrinsic Motivation has a positive and significant effect on Employee Performance, There is an effect of Compensation and Extrinsic Motivation on Employee Performance at PT Kharisma Berkah Nusantara Bekasi West Java Proven by the regression equation Y = 533.208 + 0.007 X1 + 0.264 X2., the value of the correlation coefficient (R) is 0.571 which means that the coefficient between the variables of Organizational Culture and Communication on Employee Performance is moderate, It is known that the value of the determination coefficient (KD) =(R2) x 100% is obtained from R, namely KD = 0.326 x 100% = 32.6%. while the remaining 67.4% (100%- 32.6%) is the influence of other factors that are not studied, the output is known to be Fcal of 13,754 and the significance value is 0 while the value is 4.01 So it can be concluded that Fcal > Ftabel (13,754 > 4.01)) and the significance of < 0.05 (0 < 0.05), then Ha is accepted, so it can be concluded that together it affects Employee Performance